Short Empirical Insight: Leadership and Artificial Intelligence in the Pharmaceutical Industry - Hu, Chunjia; Mohi Ud Din, Qaiser; Zhang, Li (Engineering, Technology & Applied Science Research, 2024)
This study aims to analyze the importance of the emerging idea of green talent management and its effect on employees’ innovative work behavior. In addition, the study examines how ethical leadership and artificial intelligence influence Pakistan’s pharmaceutical industry. Four hundred and seven (407) survey forms were gathered from the management departments of five pharmaceutical industries in the twin cities of Pakistan (Islamabad and Rawalpindi). The data collected were analyzed using PLS-SEM with the help of Smart PLS. The empirical evidence presented in this study supports the notion that green talent management significantly affects employees’ innovative work behavior. Furthermore, the results reveal that ethical leadership and artificial intelligence are crucial in regulating the connection between green talent management and innovative work behavior. This study provides managerial and theoretical implications derived from its results. These implications can help leaders in pharmaceutical industries effectively leverage green talent management to stimulate innovative work behaviors of their employees and attain a competitive edge in their respective marketplaces. Several studies focused on addressing the difficulties faced by organizational leaders in cultivating and maintaining people who can make valuable contributions to their companies and help gain a competitive edge in their markets. However, studies that investigate these risks are limited.